(RETRACTED) Pengaruh Perceived Organizatonal Support, Kepuasan Kerja, Dan Komitmen Organisasi Terhadap Intention To Quit Pada Generasi Y (Millennials) - Endhar Priyo Utomo (Business Management Analysis Journal (BMAJ), 2019)
Reasons for retraction:The editors retracted this article due to publication ethics misconducted by authors (authors copied another persons paper and admited it as his work).